Imbalance of the CD226/TIGIT Immune Checkpoint Is Involved in the Pathogenesis of Primary Biliary Cholangitis - Deng, Chuiwen; Li, Wenli; Fei, Yunyun; Wang, Li; Chen, Yingying; Zeng, Xiaofeng; Zhang, Fengchun; Li, Yongzhe (Frontiers in Immunology, 2020)
The relationship between the cluster of differentiation 226 (CD226)/T cell Ig and ITIM domain (TIGIT) immune checkpoint and primary biliary cholangitis (PBC) pathogenesis is unknown. Herein, PBC patients (n=42) showed significantly higher proportions of peripheral CD8+ T and CD4+ T cells expressing either CD226 or TIGIT than disease (n=25) and healthy (n=30) controls. The percentage of CD8+TIGIT+ T cell was negatively associated with total bilirubin, direct bilirubin, total bile acid, γ-glutamyl transpeptidase, and alkaline phosphatase, but positively correlated with platelet count; alkaline phosphatase was positively associated with the frequency of CD8+CD226+ T cell; and the CD226/TIGIT ratio of CD8+ T cell was positively associated with total bilirubin, direct bilirubin, total bile acid, γ-glutamyl transpeptidase, alkaline phosphatase, and aspartate aminotransferase to platelet ratio, but negatively correlated with albumin and platelet count. The effector function of CD8+CD226+ T cells was more robust than the CD8+CD226- counterparts. CD226 blockade reduced CD107a+, IFN-γ+, and TNF-α+ proportions among CD8+CD226+ T cells, inhibiting CD8+ T cell proliferation. In conclusion, CD226/TIGIT immune checkpoint imbalance is involved in the pathogenesis of PBC. The CD226/TIGIT ratio of CD8+ T cell is a potential biomarker for evaluating the disease status and the prognosis of PBC patients. Moreover, CD8+CD226+ T cells represent a possible therapeutic target for PBC, and blocking CD226 could inhibit the activity of this cell subset in vitro.